Dinamika Gender dan Peran Perempuan dalam Ekonomi Keluarga - Mujahidah Mujahidah (Al-Ulum, 2010)
This paper describes the dynamics of gender discourse and the discourse that hasmanaged to penetrate paternalistic culture. Gender discourse drew the attention ofmany parties, even the mainstream has become a significant influence on socialchange. Gender struggles and movements have paved the public perception ofwomen as weak creatures are subordinated to the social reality of society.Pragmatically, the dynamic of gender has influenced the relationship between menwith the women in the marital status. Acknowledgment of gender equality hasopened up the space between the husband and wife in the same position in mattersof rights and obligations in the conduct of family life. It is including responsibility ofprotection, safety, welfare, and living for the family.